Measuring effectiveness of sales force management remotely in Transcom Beverages Ltd in pandemic situation. - Rezwan, Resham Rahman (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.